Mechanisms and environmental factors shaping the ecosystem of brain macrophages - Penati, Silvia; Brioschi, Simone; Cai, Zhangying; Han, Claudia Z.; Colonna, Marco (Frontiers in Immunology, 2025)
Brain macrophages encompass two major populations: microglia in the parenchyma and border-associated macrophages (BAMs) in the extra-parenchymal compartments. These cells play crucial roles in maintaining brain homeostasis and immune surveillance. Microglia and BAMs are phenotypically and epigenetically distinct and exhibit highly specialized functions tailored to their environmental niches. Intriguingly, recent studies have shown that both microglia and BAMs originate from the same myeloid progenitor during yolk sac hematopoiesis, but their developmental fates diverge within the brain. Several works have partially unveiled the mechanisms orchestrating the development of microglia and BAMs in both mice and humans; however, many questions remain unanswered. Defining the molecular underpinnings controlling the transcriptional and epigenetic programs of microglia and BAMs is one of the upcoming challenges for the field. In this review, we outline current knowledge on ontogeny, phenotypic diversity, and the factors shaping the ecosystem of brain macrophages. We discuss insights garnered from human studies, highlighting similarities and differences compared to mice. Lastly, we address current research gaps and potential future directions in the field. Understanding how brain macrophages communicate with their local environment and how the tissue instructs their developmental trajectories and functional features is essential to fully comprehend brain physiology in homeostasis and disease.